THE BLOODLESS COUP OF SALĀH AL-DĪN AL-AYYŪBI - Ramdane, Tahraoui; Souad, Merah (2013)
Establishment of the Sunni Ayyūbid state in Egypt.  Relationship between curriculum of the and Ayyubid state and its adopted madhab.  Educational practices: Institutions, Curriculum, Ranks & status of scholars, Students and their social background. Financing of education.